Dysplastic bone marrow changes during maintenance therapy for acute leukemia. - Chinello, Matteo; Naviglio, Samuele; Shardlow, Alison; Severino, Alessandro; Ventura, Alessandro; Locasciulli, Anna (J Pediatr Hematol Oncol, 2015)
We describe the case of an 8-year-old girl with common precursor B-cell acute lymphoblastic leukemia who presented with severe pancytopenia during maintenance therapy with methotrexate and 6-mercaptopurine. The bone marrow smear showed moderate hypocellularity and trilinear dysplastic changes consistent with a diagnosis of drug toxicity, with no evidence of lymphoblasts. Flow cytometric immunophenotyping was negative for leukemic cells. Blood cell counts normalized after treatment with folinic acid. Maintenance therapy was gradually restarted and she remained well at follow-up visits. Myelotoxicity from methotrexate and 6-mercaptopurine may represent an unpredictable incident during an otherwise uneventful maintenance therapy, and may occur independently of other organ toxicities.
Keywords: 6-Mercaptopurine; Antineoplastic Combined Chemotherapy Protocols; Bone Marrow Diseases; Child; Disease Management; Female; Follow-Up Studies; Humans; Methotrexate; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Prognosis